2021
DOI: 10.1017/s0007114521003615
|View full text |Cite
|
Sign up to set email alerts
|

Association between sitting/lying down, standing, walking time and number of steps per day with the hormonal profile and resting energy expenditure of women with obesity living in a low-income region

Abstract: Reducing sedentary behaviour (SB) and increasing physical activity (PA) by sitting less and standing/walking more is advised to prevent chronic diseases. However, the mechanisms underlying this recommendation are not well-established, especially in individuals with obesity living in low-income regions. The present study evaluated whether there are associations between PA indicators (PAI – standing time, walking time, and the number of steps/day) and SB indicators (SBI - sitting/lying down time) with the hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 43 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…Publication dates ranged from 2001 to 2021. Out of 23 studies, 14 studies were cross-sectional designs [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and 9 were interventional studies [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] (random experiment: 5 [ 51 , 52 , 54 , 56 , 57 ] and non-random experiment: 4 [ 50 , 53 , 55 , 58 ]). Intervention length ranged from 1 week [ 55 ] to 24 months [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Publication dates ranged from 2001 to 2021. Out of 23 studies, 14 studies were cross-sectional designs [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and 9 were interventional studies [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] (random experiment: 5 [ 51 , 52 , 54 , 56 , 57 ] and non-random experiment: 4 [ 50 , 53 , 55 , 58 ]). Intervention length ranged from 1 week [ 55 ] to 24 months [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total sample size was 2105, ranging from 10 [ 55 ] to 535 [ 42 ] participants. The mean age ranged from 21.4 [ 50 ] to 62.8 years [ 49 ], with 8 studies [ 36 , 38 , 39 , 43 , 45 , 47 , 48 , 50 ] focused on the young and 10 studies focused on the middle-aged [ 37 , 41 , 42 , 44 , 49 , 51 , 52 , 56 , 57 , 58 ]. There were 11 studies that reported menstrual status, with 4 including post-menstruation [ 37 , 49 , 52 , 56 ], 5 including pre-menstruation [ 38 , 39 , 41 , 43 , 45 ], and 2 including both [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations